2019
DOI: 10.1029/2018jb016517
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Tectonic Tremor Activity Observed Over Multiple Slow Slip Cycles in the Mexican Subduction Zone

Abstract: We develop a single-station tremor spectrum template detection method that we applied to continuous seismic data recorded by the Mexican National Seismological Service broadband stations. This allows for an unprecedented long-term analysis of tectonic tremor in Mexico over multiple slow slip events (SSEs). We only detect tremor that are within previously discovered tremor regions, thereby extending the catalog in time but not space. The resulting catalog demonstrates the strong correlation of bursts of tremor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 35 publications
3
47
4
Order By: Relevance
“…The 2006 M 7.5 slow slip event is an intermittent sequence of M 6 slow transients ( 12 ). The characteristic size of these slow transients echoes the recently reported characteristic rates of tectonic tremor activity during both major and small slow slip events ( 23 ). The magnitude-frequency distribution of slow transients is not well represented by an earthquake-like power law and rather appears to have a characteristic size (fig.…”
Section: Discussionsupporting
confidence: 82%
“…The 2006 M 7.5 slow slip event is an intermittent sequence of M 6 slow transients ( 12 ). The characteristic size of these slow transients echoes the recently reported characteristic rates of tectonic tremor activity during both major and small slow slip events ( 23 ). The magnitude-frequency distribution of slow transients is not well represented by an earthquake-like power law and rather appears to have a characteristic size (fig.…”
Section: Discussionsupporting
confidence: 82%
“…Other techniques, such as the reference spectrum method (Miyazawa 2012), might be useful for detection; however, in this case, a dense seismic network for a statistical test and a reference event are required. This situation does not mean that no transiently triggered tremors occurred in other areas because Husker et al (2019) found clear signs of tremor burst, particularly in Oaxaca subsequent to the 2017 Tehuantepec earthquake, and the activity might have started during the passage of the seismic waves.…”
Section: Detection Of Triggered Tremorsmentioning
confidence: 96%
“…Other techniques, such as the reference spectrum method (Miyazawa 2012), might be useful for detection; however, in this case, a dense seismic network for a statistical test and a reference event are required. This situation does not mean that no transiently triggered tremors occurred in other areas because Husker et al (2019) found clear signs of tremor burst, particularly in Oaxaca subsequent to the 2017 Tehuantepec earthquake, and the activity might have started during the passage of the seismic waves.…”
Section: Detection Of Triggered Tremorsmentioning
confidence: 96%
“…The 2017 Tehuantepec earthquake occurred at 04:49:46.7 on September 8, 2017 (UTC) (global centroid moment tensor (CMT) catalog), in the southern Mexican subduction zone with a mechanism of normal faulting within the Cocos Plate and ruptured the whole thickness of the Cocos Plate down to the mantle (e.g., Melgar et al 2018;Suárez et al 2019) (Figure 1). Notably, the 2017 Tehuantepec earthquake is also known to have triggered tremors along the western coast of North America (Chao et al 2017) and activated tremors in the southern Mexican subduction zone (Husker et al 2019). In the southern Mexican subduction zone, tremors were triggered by the 2010 Mw8.1 Maule earthquake accompanied by slow slip (Zigone et al 2012).…”
Section: Introductionmentioning
confidence: 99%